Radikalita chirurgické lécby a postavení adjuvantní chemoterapie u nádorů ovaria hranicní malignity - Sevcík, L; Klát, J; Koliba, P; Curík, R (Ceska gynekologie, 2004)
OBJECTIVE: Evaluation of the benefit of the radical surgical therapy in the assessment of prognostic factors and indication of adjuvant therapy in patients with borderline tumors of ovary. DESIGN: Retrospective study. SETTING: Department of Obstetrics and Gynecology, University Hospital, Ostrava. METHODS: The group consists of 26 patients operated on our department, 12 of which underwent restaging operation after insufficient primary surgery in different hospital and 14 underwent primary surgery in our department. The average age was 42.9 years. RESULTS: Radical surgery with regional lymphadenectomy was performed in 18 cases (69%) and non-radical in 8 cases (31%). In 7 patients (27%) fertility preservation operation was done. According to histological results 19 tumors (73%) were of serous type, 7 being of mucinous type (27%). There were no other histological types in our group. The lymphnodes were positive in 4 cases (22%) out of 18. Eight patients were indicated for adjuvant chemotherapy (31%), 4 of them for regional lymphnodes positivity, 2 for peritoneal implants, 1 patient for tumor residuum. The last case was a patient with tumor duplicity of a borderline tumor of ovary stage FIGO IIC and corporal carcinoma stage FIGO IB. We had one case of recurrence after fertility preservation surgery. There was no case of pregnancy yet. CONCLUSIONS: Borderline tumors of ovary have good prognosis and low recurrence rate. In spite of that, there exists a group of women with higher risk of recurrence and disease progression which can be fatal. These patients may benefit from adjuvant therapy, which is indicated after evaluation of risk factors ideally acquired from the radical surgery.
Keywords: adjuvantní chemoterapie; Chemotherapy, Adjuvant; lymfadenektomie; Female; Aged; Adult; dospělí; protokoly protinádorové kombinované chemoterapie; nádory vaječníků; Ovarian Neoplasms; Humans; ženské pohlaví; senioři; lidé; Middle Aged; lidé středního věku; Lymph Node Excision; Antineoplastic Combined Chemotherapy Protocols